When do toddlers point during mealtime?: Pointing in the second year of life in everyday situations - Kasuya, Jun; Nonaka, Tetsushi (Frontiers in Psychology, 2023)
The present study aimed to gain insight into the development of the infant’s awareness of others’ attention that takes place in everyday contexts. We examined the relation between the toddler’s pointing, the toddler’s visual attention to the caregiver, and the context of the action of the caregiver in the same child-caregiver dyads at two time points (13 months and 17 months of age) during lunchtime at a Japanese daycare center, in which toddlers ate lunch with the help of caregivers. Specifically, we focused on the question of whether the timing of the toddler’s pointing reflected the ongoing context of the action of the caregiver, based on the analysis of what the caregiver was doing when a toddler exhibited pointing behavior. Our analysis revealed several interrelated results. First, the toddler’s pointing behavior was related to the visual exploration of the face of the caregiver at 17 months of age, which was not obvious at 13 months of age. Second, toddlers were more likely to point when the caregivers were just looking at them without being engaged in other salient goal-directed activities. Third, toddlers were less likely to exhibit pointing behavior when the caregivers were manipulating objects or feeding the toddlers. Taken together, the results suggested that toddlers were increasingly aware of the dynamic context of social partner’s engagement, differentiating the right time to modulate the attention of others by pointing in everyday situations. The present study supplemented the existing knowledge about pointing and the development of shared intentionality based on controlled experiments by providing a description of the context in which toddlers tend to point in the naturalistic situation of lunchtime within a specific cultural setting during the second year of life.